(untitled) (Research, Society and Development, 2021)
Associated with functional impairment and impaired physical and mental health, depression is characterized as a multifactorial mood disorder. In the clinic there is sadness, pessimism, low self-esteem, lack of pleasure, mood swings and suicidal thoughts and acts. Therefore, this narrative review aims to understand depression in the medical-student environment and associated factors. It was researched: “depression”; “Depression in medical students”; “Depression among medical students” in Bireme, PubMed and Scielo. A total of 431 articles were found, from 2012 to 2019, and 14 responded to: “how did depression manifest itself among medical students?”. Studies show a high risk for physicians and medical students to develop mental exhaustion, depressive symptoms, alcohol abuse, and a tendency to commit suicide. As for students, medical schools require a strenuous routine, with little leisure. Added to this is the pressure from parents and teachers and the fear of failure. At least 25% of medical students have some kind of psychological distress originated in academic training. Mayer found depressive symptoms in 41% of students; 81.7% presented state anxiety and 85.6%, trait anxiety. Souza noted a predominance of depression in medical students than in the general population. Faced with this susceptibility, teachers must be able to recognize depressive signs and symptoms in students so that there is an early and effective intervention.